2012
DOI: 10.1038/ajh.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia Increases Placenta Endothelin-Converting Enzyme-1 Expression in Trophoblasts

Abstract: ECE-1 and ET-A are expressed in the trophoblastic cells of the placenta and MT. This may affect local endothelin levels, BP and IUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…Bursztyn's group performed a series of studies to evaluate the effects of chronic hyperinsulinemia during gestation. 15,16,[26][27][28] As expected, they observed that pregnant rats treated with insulin 1 week before and throughout pregnancy by subcutaneously implanted sustained-release insulin pellets had elevated serum insulin levels (approximately 78%) compared with normal pregnant rats. 15 They showed that systolic blood pressure measured by tail cuff was increased in insulin-treated pregnant rats on GD 19 and 20.…”
Section: Discussionsupporting
confidence: 60%
“…Bursztyn's group performed a series of studies to evaluate the effects of chronic hyperinsulinemia during gestation. 15,16,[26][27][28] As expected, they observed that pregnant rats treated with insulin 1 week before and throughout pregnancy by subcutaneously implanted sustained-release insulin pellets had elevated serum insulin levels (approximately 78%) compared with normal pregnant rats. 15 They showed that systolic blood pressure measured by tail cuff was increased in insulin-treated pregnant rats on GD 19 and 20.…”
Section: Discussionsupporting
confidence: 60%
“…Subsequent studies in this model showed that insulin reduced PlGF and arrested trophoblast invasion in the uterus (168). Intriguingly, it was noted that the trophoblasts in placentas from the hyperinsulinemic rats expressed greater endothelin converting enzyme (82). The major cleavage product of this enzyme is ET-1.…”
Section: Effects Of Obesity On the Placental Function And Perfusionmentioning
confidence: 96%
“…Sabe-se que os fatores circulantes maternos, como nutrientes, metabólitos e hormônios apresentam papel fundamental durante a gestação pois, dentre outras funções, regulam o desenvolvimento da placenta. Os níveis de insulina séricos maternos, por exemplo, apesar de não atravessarem a barreira placentária para que possam exercer alguma função direta nos órgãos fetais, quando em altas concentrações, podem alterar a função placentária (150)(151)(152).…”
Section: A Prole De Mães Resistentes E Propensas à Obesidade Apresent...unclassified